2009
DOI: 10.1086/605495
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin Resistance

Abstract: With increasing pressure to prevent methicillin-resistant Staphylococcus aureus (MRSA) infection, it is possible that there will be increased use of mupirocin for nasal decolonization of MRSA. Understanding the mechanisms, clinical significance, and epidemiology of mupirocin resistance is important for predicting how changes in mupirocin use may affect bacterial populations and MRSA control. High-level mupirocin resistance in S. aureus is mediated by a plasmid-encoded mupA gene. This gene can be found on conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
186
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(192 citation statements)
references
References 56 publications
1
186
2
3
Order By: Relevance
“…26,38 Additionally, repeated decolonization with mupirocin may select for a mupirocin-resistant MRSA-population. 32 Persistent staphylococci carriage and intermittent staphylococci colonization in humans is well described and occurs in about 30% and 60% of the population, respectively. 21 Intermittently, colonized people are colonized with different S. aureus strains at varying frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…26,38 Additionally, repeated decolonization with mupirocin may select for a mupirocin-resistant MRSA-population. 32 Persistent staphylococci carriage and intermittent staphylococci colonization in humans is well described and occurs in about 30% and 60% of the population, respectively. 21 Intermittently, colonized people are colonized with different S. aureus strains at varying frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported that the elimination of nasal S. aureus by 63% with mupirocin, the emergence of resistant strains to this antibiotic from infected individuals is possible [28]. The increase of mupirocin resistant S. aureus as an attempt to eliminate methicillin resistant strains [29].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of mupirocin resistant S. aureus as an attempt to eliminate methicillin resistant strains [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the protein synthesis inhibitor mupirocin is currently widely used for anti-MRSA nasal decolonisation, it is not active against non-multiplying persister bacteria which constitute a reservoir for recolonisation [5] . In addition to this, an increased prevalence of mupirocin resistant MRSA [6] has led to the development of more effective alternatives, including the experimental antimicrobials LTX-109 [7] and XF-73 [8] in addition to HT61 [1] .The mode of action of HT61 has not hitherto been thoroughly investigated, however initial cell-based assays showed that HT61 is capable of depolarising the cytoplasmic membrane ofGram positives with further evidence from electron microscopy suggesting that HT61 causes lysis of either the membrane or cell wall [1,4] . The putative membrane-targeting of HT61 may provide some explanation for its potency against non-multiplying MRSA [9] , and suggests that its mechanism of action may be similar to those of other membrane-active antibiotics such as daptomycin [10] , cationic antibiotics such as polymyxins B and E (colistin), gramicidin S [11] and cationic antimicrobials, for example chlorhexidine [12] and ceragenins [13] .…”
mentioning
confidence: 99%